2021
DOI: 10.3390/w13060838
|View full text |Cite
|
Sign up to set email alerts
|

Portraying the Water Crisis in Iranian Newspapers: An Approach Using Structure Query Language (SQL)

Abstract: Water is a valuable resource for which demand often exceeds supply in dry climates. Managing limited water resources becomes increasingly difficult in circumstances of recurring drought, rising populations, rapid urbanisation, industrial development, and financial constraints, such as occur in Iran. Newspapers both report on and influence people’s understanding of water-related issues. An analysis was undertaken of two major Iranian daily newspapers over a 7-year period. Structure Query Language (SQL) was empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Researchers (with 14% share) were not the main contributors in writing wildlife articles for the sampled newspapers. Similarly, it was found that researchers had the lowest contributions in writing general ‘environmental’ news items (10%) [ 52 ] and ‘water’ news items (9%) in Iranian newspapers [ 59 ]. These findings are in accordance with those reported by Rust [ 61 ], who found that academics did not show interest in writing news on the human–wildlife conflict in Namibia (2% share).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers (with 14% share) were not the main contributors in writing wildlife articles for the sampled newspapers. Similarly, it was found that researchers had the lowest contributions in writing general ‘environmental’ news items (10%) [ 52 ] and ‘water’ news items (9%) in Iranian newspapers [ 59 ]. These findings are in accordance with those reported by Rust [ 61 ], who found that academics did not show interest in writing news on the human–wildlife conflict in Namibia (2% share).…”
Section: Discussionmentioning
confidence: 99%
“…Educating: the lowest numbers of wildlife items in our sampled newspapers were related to the message described as educating. In earlier research on ‘general environmental’ and ‘water’ news items, it was noted that the educating news items were the lowest, with 9% [ 52 ] and 2% [ 59 ], respectively. Media outlets must play a role as educators as part of their essential functions [ 19 ], though they must be treated with caution when considered for public education about wildlife [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Queries are essential mechanisms for users who are consulting database systems [38]. A similar method had been used before to examine the role of newspaper articles in transmitting environmental news to the public [39][40][41], and searching for thematic areas of research on land degradation and desertification at the global level [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to other groups, they may have less inclination to be involved in this medium. Analysis of Iranian newspapers, for example, showed that researchers had the lowest share in writing on topics related to general environmental issues (10%) and water (9%) [34,35]. This low participation of researchers is more or less the same elsewhere in the world.…”
Section: Productionmentioning
confidence: 99%